Enhancing bone regeneration using kaempferol as an osteoprotective compound: signaling mechanisms, delivery strategies, and potential applications - Mojdeh Salehi Namini; Sanam Mohandesnezhad; Sadaf Mohandesnezhad; Vahid Mansouri; Lobat Tayebi; Nima Beheshtizadeh (Journal of Biological Engineering)
Abstract Various plants, including fruits, vegetables, and spices, contain kaempferol, a bioflavonoid compound with diverse medicinal effects, such as antioxidant, antibacterial, and anti-inflammatory characteristics. Furthermore, this compound exhibits multiple health-promoting properties, including osteoprotection and osteogenesis, primarily by modulating various cell-signaling pathways. This review aims to illustrate the medical advantages of kaempferol and its role in regulating bone metabolism through cell signaling mechanisms. Numerous studies have demonstrated the bone-protective properties of kaempferol and its encapsulated form. Further research is needed to clarify the optimal dosages, toxicity, safety, and other potential mechanisms of action. This review demonstrates that several signaling pathways, including nuclear factor-kappa B (NF-κB), estrogen receptor, mitogen-activated protein kinase (MAPK), bone morphogenetic protein-2 (BMP-2), and mammalian target of rapamycin (mTOR) signaling pathways, regulate the osteogenesis and anti-osteoporotic effects of kaempferol as an osteoprotective compound. However, the main limitations to applying kaempferol in bone-related disorders are its low stability and absorption. One of the promising approaches to increasing its effectiveness is using delivery-related strategies such as encapsulation, scaffolding, hydrogels, and liposomes to constantly release kaempferol and subsequently enhance its bioavailability and absorption. Thus, this review has attempted to exhibit the understanding of the benefits of kaempferol as a new compound in regulating bone-related signaling pathways and various available delivery approaches to improve its therapeutic potential for treating bone-related diseases.